Direct Attribution in Omani Tenders Law: A Jurisprudential Study - Al-Jahwari, Saif Sulaiman Amer (Journal of Islamic Sciences, 2022)
This study aimed at Research and clarify the reality of Direct Attribution in the Omani Tender Law in an Islamic Jurisprudential (Fiqh) Study. It aims to study its juristic and legal adaptation under explanation of the legal controls for Direct Attribution in the Omani Tender Law and the extent of their compatibility with Shariah guidelines in Islamic jurisprudence.Research Results:- Direct Attribution is one of the alternative methods for public tender in the Omani Tender Law, which apply in the government institutions in normal and emergency cases, and it is a financial compensation contract, not just an agreement or a promise.- The conditions associated for the control of Direct Attribution, such as the penal terms and contract guarantee, are appropriate conditions for the contract, because they achieve a legitimate interest in the contract in terms of ensuring what this contract entails, whether it is the supply, consulting services, transportation or manufacture.- Direct attribution contracts are subject to monopoly and deception by the contractor or supplier by exploiting the needs of government institutions to increase the price manifold.
Keywords: direct attribution; tenders law; Sultanate of Oman; legal controls; Islamic jurisprudence